Featured Cover. Issue 11 (11th October 2021) - Wang, Jie; Ao, Qiong; Peng, Yangfeng; Feng, Cai
Abstract : The cover image is based on the Research Article Diastereomeric resolution of 3‐chloromandelic acid with threo‐(1S, 2S)‐2‐amino‐l‐p‐nitrophenyl‐1, 3‐propanediol by Jie Wang et al., https://doi.org/10.1002/chir.23357 .